ANALISIS PRAKTIK IKHTIKAR MENURUT IMAM YAHYA BIN UMAR DAN RELEVANSINYA TERHADAP UNDANG-UNDANG PENIMBUNAN BARANG DI INDONESIA - Amalia, Maya Riski (RJABM (Research Journal of Accounting and Business Management), 2024)
AbstrackThe purpose of this research is to determine the practice of Ihtikar according to the thoughts of Imam Yahya Bin Umar and its relevance to the Law on Hoarding of Goods in Indonesia. This research uses a literature review in the form of searching and using previous research to answer the practice of Ihtikar according to the thoughts of Imam Yahya bin Umar and its relevance to cases of hoarding of goods in Indonesia. The results of the research indicate that Ihtikar Thought according to Imam Yahya bin Umar is very relevant to the laws in force in the country. According to Imam Yahya bin Umar, Ihtikar is a crime because it causes harm, so this practice is strictly prohibited. This is also in accordance with Indonesian law where in our country, the practice of Ihtikar is strictly prohibited because it can make people miserable. This prohibition is stated in Article 29 of Law no. 7 of 2014 concerning Trade.  Keyword:  Ihtikar, Indonesian Goods Hoarding Law